A Rare Case of Persistent Bacteremia: Leadless Micra Pacemaker Endocarditis - Himax Patel; Sean Harrell; Haitham Hreibe; Musa Sharkawi; Wael AlJaroudi (Case Reports in Cardiology)
Leadless pacing systems have revolutionized the field of electrophysiology given its low complication rates and almost non-existent rate of infections compared with traditional pacemakers. These devices boast resistance to infections given its unique features; however, as described in this report, device-related infection from these leadless devices is still possible. In patients with leadless pacing system that is persistently bacteremic in the future, evaluation of the device with transesophageal echocardiogram or intracardiac echocardiography should be performed, and if vegetation is noted on the device, device extraction should highly be considered, along with empiric intravenous antibiotics. Lastly, new leadless device should not be re-implanted within 2 weeks of the removal of the infected device to prevent seeding of the new device.